Laser-Induced Breakdown Spectroscopy (LIBS)를 이용한 방사성 스트론튬 오염물질에 대한 신속한 모니터링 기술 - 박진영(Jin young Park); 김현아(Hyun a Kim); 박기홍(Ki hong Park); 김경웅(Kyoung woong Kim) (자원환경지질, 2017)
Along with Cs-137 (half-life: 30.17 years), Sr-90 (half-life: 28.8 years) is one of the most important environmental monitoring radioactive elements. Rapid and easy monitoring method for Sr-90 using Laser-Induced Breakdown Spectroscopy (LIBS) has been studied. Strontium belongs to a bivalent alkaline earth metal such as calcium and has similar electron arrangement and size. Due to these similar chemical properties, it can easily enter into the human body through the food chain via water, soil, and crops when leaked into the environment. In addition, it is immersed into the bone at the case of human influx and causes the toxicity for a long time (biological half-life: about 50 years). It is a very reductive and related with the specific reaction that makes wet analysis difficult. In particular, radioactive strontium should be monitored by nuclear power plants but it is very difficult to be analysed from high-cost problems as well as low accuracy of analysis due to complicated analysis procedures, expensive analysis equipment, and a pretreatment process of using massive chemicals. Therefore, we introduce the Laser-Induced Breakdown Spectroscopy (LIBS) analysis method that analyzes the elements in the sample using the inherent spectrum by generating plasma on the sample using pulse energy, and it can be analyzed in a few seconds without preprocessing. A variety of analytical plates for samples were developed to improve the analytical sensitivity by optimizing the laser, wavelength, and time resolution. This can be effectively applied to real-time monitoring of radioactive wastewater discharged from a nuclear power plant, and furthermore, it can be applied as an emergency monitoring means such as possible future accidents at a nuclear power plants. Cs-137 (반감기 : 30.17년)과 더불어 중요한 원자력발전소 주변 환경감시대상 방사성 핵종 가운데 하나인 순수한 베타방출체인 Sr-90 (반감기 : 28.8년)에 대한 신속하고 용이한 모니터링 방법을 연구하였다. 스트론튬은 칼슘과 같은 2족 알칼리 토금속에 속해 있어서 전자배치나 크기가 비슷하며 최외각전자를 2개 가지고 있기 때문에 화학적으로 칼슘과 치환될 수 있다. 이러한 유사한 화학적 성질로 인해서 환경으로 유출시 물, 토양 및 농작물을 통한 먹이사슬을 거쳐서 인체로 쉽게 유입될 수 있으며, 인체 유입 시 뼈에 쉽게 침적되어 장기간 (생물학적 반감기 : 약 50년) 동안 독성을 유발한다. 스트론튬은 매우 환원성이 있고 특이 반응으로 습식분석이 어려우며, 특히 원자력발전소에서 감시하고 있는 방사성 스트론튬은 복잡한 분석절차, 고가의 분석 장비 사용 및 화학 전처리약품 다량 사용 등으로 분석의 정확도 저하는 물론 고비용에 따른 문제를 안고 있다. 따라서 펄스에너지를 사용하여 시료에 플라즈마를 생성시켜 고유 스펙트럼을 이용해 시료내 원소를 분석하는 Laser-Induced Breakdown Spectroscopy (LIBS) 분석기법을 도입하여 전처리 과정 없이 수 초 내에 분석이 가능하고 현장에서 실시간으로 측정 가능한 스트론튬 원소의 정량분석 방법을 도출하였다. 다양한 분석에 필요한 시료기판을 개발하여 레이저, 파장 및 시간분해능의 최적화로 분석 감도를 향상시키고 방해이온에 대한 영향 평가로 액체시료의 정량분석을 가능하게 하여 신속한 모니터링 체계를 구축하게 하였다. 이는 원자력발전소로부터 방출되고 있는 방사성 폐수의 실시간 모니터링에 효과적으로 적용될 수 있으며, 더 나아가 후쿠시마 원전사고와 같은 비상시 모니터링 수단으로 적용 될 수 있다.